Tools for Integrated River Flood Management (Hydraulics Modeling and Logical Framework Analysis) - C.H.J., Bong; Mah, Yau Seng; F.J., Putuhena; S., Said; R.A., Bustami (ASM Science, 2012)
Hydraulics simulation can be used as a supporting tool for planning and developing a framework, such as Integrated Flood Management for river management. To demonstrate this, a hydraulics model for the Sarawak River Basin was run using InfoWorks RS software by Wallingford Software, UK. InfoWorks River Simulation (RS) was chosen because its applicability has been proven and widely used to model Malaysian rivers. The extraction of computed floodwater level and flood maps for different time intervals would produce the rate of floodplain submergence from river bank level. This information could be incorporated into a logical framework to support decisions on flood management measures. Thus, hydraulics models can be used as tools to provide the necessary decision parameters for developing logical frameworks which would act as to guide the planning when it involved various stakeholders’ participation.